Cortical Volume in the Right Cingulate Cortex Mediates the Increase of Self-Control From Young Adult to Middle-Aged - Jiang, Lili; Li, Chunlin; Li, Yubin (Frontiers in Behavioral Neuroscience, 2022)
A high self-control capacity is related to better environmental adaptability, happy and healthy life. Neuroimaging studies have elucidated the anterior cingulate, the prefrontal cortex and the orbitofrontal cortex are involved in self-control. However, few study integrated all three measurements, age, human brain and self-control into a single quantitative model, and examined whether self-control ability increased or decreased with age. In this study, we collected 65 participants’ data including structural MRI and Tangney self-control scale to explore age dependence of cortical volume and self-control from young adult to middle-aged, as well as whether a nonlinear association in the tridimensional model of age-brain-self control was necessary to explain all the data in this study. We showed self control increased with age but cortical volume decreased with age. In a linear model, our mediation analyses revealed cortical volume in the right cingulate cortex mediated the increase of self-control; we also constructed a general nonlinear model of age-brain-behavior and proved that the inverted development of human brain morphology and self-control abilities happened when morphology decays with age at a relatively small rate. Our study indicated healthy aging in terms of increasing self-control is achievable, and our quantitative linear model of self-control laid theoretical foundations for studies on nonlinear associations in age-brain-behavior.